Debt stocks, debt flows and the balance of payments - International Working Group on External Debt Statistics (Paris : Organisation for Economic Co-operation and Development ; Washington, D.C. : OECD Publications and Information Centre [distributor], 1994)
The report begins by defining some key terms useful for the discussion of various debt classification systems of the members of the IWGEDS. A glossary of terms is also provided at the end of the report for the reader who may not be familiar with all of the concepts and terms relating to external debts, international economics and finance.
Cooperatively produced for the International Working Group on External Debt Statistics by its members.
Includes bibliographical references.
osc 25/07/2015
Loans
Keywords: Debts management; Balance of payments